Effects of monitoring for visual events on distinct components of attention - Poth, Christian H.; Petersen, Anders; Bundesen, Claus; Schneider, Werner X. (Frontiers in Psychology, 2014)
Monitoring the environment for visual events while performing a concurrent task requires adjustment of visual processing priorities. By use of Bundesen's (1990) Theory of Visual Attention (TVA), we investigated how monitoring for an object-based brief event affected distinct components of visual attention in a concurrent task. The perceptual salience of the event was varied. Monitoring reduced the processing speed in the concurrent task, and the reduction was stronger when the event was less salient. The monitoring task neither affected the temporal threshold of conscious perception nor the storage capacity of visual short-term memory nor the efficiency of top-down controlled attentional selection.